Revealing Context-Specific Conditioned Fear Memories with Full Immersion Virtual Reality - Huff, Nicole; Alba Hernandez, Jose; Fecteau, Matthew; Zielinski, David; Brady, Rachael; LaBar, Kevin S. (Frontiers in Behavioral Neuroscience, 2011)
The extinction of conditioned fear is known to be context specific, and often referred to as more robustly contextually bound than the fear memory itself (Bouton, 2004). Yet, recent findings in rodents have challenged the notion that contextual fear retention is initially generalized. The context specificity of a cued-fear memory to the learning context has not been addressed in the human literature largely due to limitations in methodology. Here we adapt a novel technology to test the context specificity of cued fear conditioning using full immersion 3-dimensional virtual reality (VR). During acquisition training, healthy participants navigated through virtual environments containing dynamic snake and spider conditioned stimuli (CSs), one of which was paired with electrical wrist stimulation. During a 24-hour delayed retention test, one group returned to the same context as acquisition training whereas another group experienced the CSs in a novel context. Unconditioned stimulus (US) expectancy ratings were assayed on-line during fear acquisition as an index of contingency awareness. Skin conductance responses (SCR) time-locked to CS onset were the dependent measure of cued fear, and skin conductance levels during the interstimulus interval were an index of context fear. Findings indicate that early in acquisition training, participants express contingency awareness as well as differential contextual fear, whereas differential cued fear emerged later in acquisition. During the retention test, differential cued fear retention was enhanced in the group who returned to the same context as acquisition training relative to the context shift group. The results extend recent rodent work to illustrate differences in cued and context fear acquisition and the contextual specificity of recent fear memories. Findings support the use of full immersion VR as a novel tool in cognitive neuroscience to bridge rodent models of contextual phenomena underlying human clinical disorders.